(untitled) (Research, Society and Development, 2022)
Laryngeal trauma is a penetrating injury in the cervical region with great importance in emergency care. Penetrating injuries are associated with ballistic trauma, with a greater chance of endolaryngeal rupture. This case report refers to a male patient who suffered a penetrating injury caused by a firearm in the anterior cervical region with a complex laryngeal lesion, grade IV of Legacy Emanuel. He underwent an emergency cervicotomy with evidence of thyroid cartilage injury, and a cartilaginous graft was performed from the second right costochondral joint, and the patient progressed satisfactorily in the postoperative period without functional speech deficits. It was demonstrated that the application of the technique resulted in the non-rejection of the organ to the graft, with rapid recovery. There was complete epithelialization of the intraluminal face of the graft on the fifth postoperative day evidenced by bronchoscopy and resulting in functional and aesthetic gain for the patient, in addition to a shorter hospital stay. This adopted strategy generated good results without flap rejection, with good aesthetic repercussions and without functional limitations in the patient, reducing the number of surgical approaches, hospitalized time and expenditure of financial resources with hospitalization.